Can Vitamin D Positively Impact COVID-19 Risk and Severity Among Older Adults: A Review of the Evidence - Marks, Ray (Journal of Aging Research And Healthcare, 2020)
Background The coronavirus Covid-19 strain that emerged in December 2019, continues to produce a widespread and seemingly intractable negative impact on health and longevity in all parts of the world, especially, among older adults, and those with chronic health conditions. Aim The first aim of this review article was to examine, summarize, synthesize, and report on the research base concerning the possible use of vitamin-D supplementation for reducing both Covid-19 risk and severity, especially among older adults at high risk for Covid-19 infections. A second was to provide directives for researchers or professionals who work or are likely to work in this realm in the future. Methods All English language relevant publications detailing the possible efficacy of vitamin D as an intervention strategy for minimizing Covid-19 infection risk published in 2020 were systematically sought. Key words used were: Vitamin D, Covid-19, and Coronavirus. Databases used were PubMed, Scopus, and Web of Science. All relevant articles were carefully examined and those meeting the review criteria were carefully read, and described in narrative form. Results Collectively, these data reveal vitamin D is a powerful steroid like compound that is required by the body to help many life affirming physiological functions, including immune processes, but its deficiency may seriously impact the health status and well being of the older adult and others. Since vitamin D is not manufactured by the body directly, ensuring those who are deficient in vitamin D may prove a helpful overall preventive measure as well as a helpful treatment measure among older adults at high risk for severe Covid-19 disease outcomes. Conclusions Older individuals with chronic health conditions, as well as healthy older adults at risk for vitamin D deficiency are likely to benefit physically as well as mentally, from efforts to foster adequate vitamin D levels. Geriatric clinicians can expect this form of intervention to reduce infection severity in the presence of Covid-19 infection, regardless of health status, and subject to careful study, researchers can make a highly notable impact in this regard.
Keywords: Coronavirus; Covid-19; infection; immunity; older adults; prevention; therapeutic use of vitamin D